Understanding Biotechnology An Integrated and Cyber-Based Approach - Acquaah, George (Pearson/Prentice Hall, 2004)
"The only text on the market with comprehensive coverage of biotechnology at an introductory level, this timely book has an easy-to-read style that makes it suitable for those students with or without a background in biology. While emphasizing biotechnology's core principles and practices, its cyber-based approach allows a built-in mechanism for updating information in the rapidly evolving biotech field."--Pub. desc.